THE ROLE OF LEGAL EDUCATION IN REFORMING THE EDUCATION SYSTEM - Akayeva Nodira; Abulova Mohigul Komiljonzoda (Scholar Express Journal, 2022)
The article describes the process of raising the legal awareness and legal culture of young people, analyzes the role and importance of legal education and upbringing in the formation of the legal consciousness of the individual, and draws scientific and theoretical conclusions
Keywords: Legal education; legal consciousness; general secondary education; pedagogical skills